Changes of Quality of Winter Wheat During Maturing - Sipos, Péter; Tóth, Ároád; Győri, Zoltán (Acta Agraria Debreceniensis, 2005)
We analysed the flour of two winter wheat varieties to determine the effect of maturity state and grain position in the ear on the element composition of flour. Samples were taken from the 14th to the 42th day of anthesis. Ear samples were cut into three (basal, central and apical) parts, the trashed grains were milled, and the element compositions of the flours were determined.We found that the grain position within the ear has an effect on flour element content. Flours of apical grains had lower nitrogen, phosphorus and sulphur contents than flours of central and basal grains. The nutrients can be divided into two parts, based on the formation of element content during maturation. Nitrogen, sulphur and copper contents changed continuously during maturity, while the P, K, Ca, Mg, Mn, Sr and Zn contents decreased until a specific value and became nearly constant in the second half of maturity. We found that – although the nitrogen concentration of flours changed continuously – the amount of nitrogen in the flours reached a constant value for the second half of maturity.